GASTROPROTECTIVE ACTIVITY OF ETHYL ACETATE FRACTION OBTAINED FROM THE STEM BARK EXTRACT OF DESERT DATE (BALANITES AEGYPTIACA) - Ugwah-Oguejiofor, Chinenye; Ugwah, O. M. (FUDMA Journal of Sciences, 2023)
The study aimed to investigate the gastroprotective activity of the ethyl acetate fraction derived from the stem bark extract of the Desert date tree (EFDD) (Balanites aegyptiaca L. Delile; family Zygophyllaceae) using ethanol and indomethacin-induced ulcer models in Wistar rats. The study was conducted using Wistar rats and divided them into five groups (n=5). Group 1 received 10% Tween 20 (1 ml/kg), which served as the control group. Group 2 was administered the standard drug, omeprazole (20 mg/kg). Groups 3-5 were the extract groups and received doses of 125, 250, and 500 mg/kg, respectively, of EFDD. Two ulcer models were used in the study namely ethanol-induced ulcers and indomethacin-induced ulcers. After administration of the respective treatments, evaluation of the mean ulcer indices in each group and calculation of the percentage ulcer inhibition compared to the control group were carried out. The results indicated that the EFDD, at doses of 250 and 500 mg/kg, significantly reduced the mean ulcer indices in both the ethanol and indomethacin-induced ulcer models compared to the control group (p<0.05). This suggests that the EFDD possesses gastroprotective properties. In conclusion, the EFDD exhibits gastroprotective activity. This finding supports the traditional use of Desert date in folkloric medicine for the treatment of ulcers. However, further research is necessary to explore the underlying mechanisms responsible for the observed gastroprotective effects.